Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, J.; Graichen, Noah; Sulkowski, Mikolaj (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure-function analyses of the Drosophila I-Smad Dad and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring in vivo outputs of BMP signaling. We identified a critical 24-amino acid putative DNA-binding domain (DNABD) within the MH1 domain of the Drosophila I-Smad, Dad, that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNABD disrupts a beta hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity while Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Biology; Cell biology; Context (archaeology); Decapentaplegic; Drosophila melanogaster; Function (biology); Gene; Genetics; Primordium; SMAD; Signal transduction; Vertebrate; dept.bio

Tissue-specific I-Smad mechanisms revealed by structure–function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, Joshua; Graichen, Noah; Sulkowski, Mikolaj (Life Science Alliance, 2026)
Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure–function analyses of the Drosophila I-Smad, Dad, and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring outputs of BMP signaling in vivo. We identified a 24–amino acid putative DNA-binding domain within the MH1 domain of Dad that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNA-binding domain disrupts a β-hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity, whereas Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Domain (mathematical analysis); Function (biology); Homologous chromosome; Signal transduction; Vertebrate; Wing; dept.bio

Immunofluorescence and image analysis pipeline for Drosophila motor neurons - Brown, Jeremy R; Brown, Jeremy R; Phongthachit, Chanpasith; Sulkowski, Mikolaj J (Biology Methods and Protocols, 2019)
The neuromuscular junction (NMJ) of larval Drosophila is widely used as a genetic model for basic neuroscience research. The presynaptic side of the NMJ is formed by axon terminals of motor neurons, the soma of which reside in the ventral ganglion of the central nervous system (CNS). Here we describe a streamlined protocol for dissection and immunostaining of the Drosophila CNS and NMJ that allows processing of multiple genotypes within a single staining tube. We also present a computer script called Automated Image Analysis with Background Subtraction which facilitates identification of motor nuclei, quantification of pixel intensity, and background subtraction. Together, these techniques provide a pipeline for neuroscientists to compare levels of different biomolecules in motor nuclei. We conclude that these methods should be adaptable to a variety of different cell and tissue types for the improvement of efficiency, reproducibility, and throughput during data quantification. © 2019 The Author(s) 2019. Published by Oxford University Press.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/072-055-143-711-580 tex.type: [object Object]
Keywords: dept.bio; peer-reviewed

Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophil - Sulkowski, Mikolaj; Simoncek, Ani; Sviridoff, Steven; Graichen, Noah; Hays, Joshua (Zenodo (CERN European Organization for Nuclear Research), 2026)
Data from publication in Life Science Alliance
Keywords: Alliance; Context (archaeology); Set (abstract data type); dept.bio

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence